2020
DOI: 10.2528/pierm19110706
|View full text |Cite
|
Sign up to set email alerts
|

Non-Stationary Statistics With Amplitude Probability Density Function for Exposure and Energy Density Reporting Near a Mobile Phone Running 4g Applications

Abstract: Present contribution introduces, for the first time, the description of human exposure dynamics to mobile phone radiation by implementing the use of in-air integrated energy density (IED) evolution in time. Using the amplitude probability density (APD) function capability of a real-time spectrum analyzer, we demonstrate the differences in exposure due to five different mobile applications running in Long Term Evolution (LTE) standard, based on energy deposited in air: voice call; voice over LTE (VoLTE); video … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Therefore, at least voice calls deserve special attention in future dosimetric studies devoted to the biological effects of 5G signals. Previous findings, extracted by applying a different methodology but still based on real-time spectrum analyzers and small and sensitive field probes, emphasized specific features of the time variability of signals emitted by a 4G phone [28]. In line with those findings, this study allowed a step further in extracting the main peculiarities of the time dynamics of the emitted radiation, by comparing the 4G and 5G sub-6 GHz band networks using the same phone model.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Therefore, at least voice calls deserve special attention in future dosimetric studies devoted to the biological effects of 5G signals. Previous findings, extracted by applying a different methodology but still based on real-time spectrum analyzers and small and sensitive field probes, emphasized specific features of the time variability of signals emitted by a 4G phone [28]. In line with those findings, this study allowed a step further in extracting the main peculiarities of the time dynamics of the emitted radiation, by comparing the 4G and 5G sub-6 GHz band networks using the same phone model.…”
Section: Resultssupporting
confidence: 66%
“…It is reported that more than 70 million small cells will be installed worldwide by 2025, with one-third belonging to 5G systems [27]. Very few papers quantified the radiation emitted by a mobile terminal in 5G networks [28].…”
Section: Introductionmentioning
confidence: 99%
“…Statistical techniques may be used to quantify differences in the dynamics of 4G versus 5G signals, such as calculating the mean or variance of the signal over time or analyzing the distribution of the signal power over different time intervals. Moreover, Amplitude Probability Density (APD) and Complementary Cumulative Distribution Function (CCDF) analyses might help in understanding the temporal behavior of EMF signals and identifying specific high-power events that could be relevant for exposure assessment [33,34]. APD and CCDF will depend on various factors, including deployment scenarios, network configurations, and measurement conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the previously highlighted aspects retrieved from the literature survey and following some of our previous work [32,33], this article aims to underline differences in terms of user's exposure to 802.11n (2.4 GHz) and 802.11ac (5 GHz) Wi-Fi signals near a mobile phone-device under test (DUT), based on the measurements performed under different received signal strength conditions, different channel bandwidths, and traffic directions (upload/download) respectively. Authors found no such information in the analysis of the state-of-the-art literature and consider it extremely important as it may represent a milestone in developing exposure profiles, extremely valuable for future epidemiological studies.…”
Section: Introductionmentioning
confidence: 99%